Talking Mungee – a teacher, provider, connector, exemplar: what’s not to celebrate about the world’s largest mistletoe, Nuytsia floribunda - Lullfitz, Alison; Knapp, Lynette; Cummings, Shandell; Woods, Jessikah; Hopper, Stephen D. (Plant and soil, 2025)
Purpose Endemic to Noongar Country of southwestern Australia, the charismatic and much-loved mistletoe, Nuytsia floribunda (Labill.) R.Br. ex G.Don ( Munjee / Moodjar in Noongar language), was the subject of a 2010 review which explored aspects of its cultural importance and botanical attributes based largely on early colonial accounts and scientific findings. Our purpose was to apply cross-cultural methods to review and update findings reported by Hopper ( 2010 ). Methods We have recently explored this iconic species through a collaborative Elder-led, cross-cultural process, largely through oral accounts of contemporary Merningar Noongar knowledge holders. Results We record previously unpublished insights relating to Nuytsia floribunda , and longheld Noongar custom relating to its conservation, use and multi-faceted relationships with southwestern Australia’s First Nations peoples. We present Noongar- and Western science-derived knowledge relating to the physiology, ecology and evolution of this species. Conclusion The unique biology, ingenuity and physical prominence of Nuytsia floribunda has been recognised in Noongar lore for millennia. We suggest it as a valuable teacher and exemplar of prosperous survival in old, climatically-buffered, infertile landscapes and to this end, should be widely celebrated.